A study on the sparking distance in the electrochemical discharging process. (March 2022) - Chen, Yu-Jen; Sundaram, Murali
Abstract: The electrostatic force affects the gas film formation and collapsing in the electrochemical discharge process. Experimental observation of the process using a side insulated tool shows that the gas bubble will collapse or depart from the tooltip at the removal of electrostatic force. This study investigates the relationship between the electrostatic force and the sparking distance. A unique experimental method is developed in this study to establish the distance of sparking. Within this distance the electrostatic force can attract the electrolyte to the tool and result in a spark. A mathematical model is developed to predict the sparking distance under the influence of electrostatic force. Experimental verification of the model revealed that the sparking distance could be reduced by decreasing the tool size and lowering the applied voltage. The model was able to predict the trend of the average sparking distance with less than 5% variation. Electrolyte concentration has a minor effect on the sparking distance but affects the voltage range for sparking.